2019
DOI: 10.1002/pro.3733
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin presents isoform variants with altered neonatal Fc receptor interactions

Abstract: Human serum albumin (HSA) is the most abundant protein in plasma and presents the particularity, with IgG, to have an extraordinary long serum half‐life conferred by its interaction with the neonatal Fc receptor (FcRn). If the impact of IgG post‐translational modifications (PTMs) on FcRn binding is well documented, it is far less reported for HSA despite numerous PTMs occurring on the protein in plasma. HSA is susceptible to numerous degradation reactions in plasma, because of aging, oxidative stress or liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Although the principal HSA-FcRn binding interaction site is in the N-terminal domain III, domain I, which contains Cys 34 , also plays a role . FcRn affinity chromatography, ion-exchange chromatography, and surface plasmon resonance data demonstrate that modification at Cys 34 does impair FcRn binding . However, the paper from Leblanc et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the principal HSA-FcRn binding interaction site is in the N-terminal domain III, domain I, which contains Cys 34 , also plays a role . FcRn affinity chromatography, ion-exchange chromatography, and surface plasmon resonance data demonstrate that modification at Cys 34 does impair FcRn binding . However, the paper from Leblanc et al .…”
Section: Discussionmentioning
confidence: 99%
“…60 FcRn affinity chromatography, ion-exchange chromatography, and surface plasmon resonance data demonstrate that modification at Cys 34 does impair FcRn binding. 61 However, the paper from Leblanc et al does not report binding affinities of specific HSA adducts, but rather that a plasma-derived fraction of HSA consisting of a variety of HSA isoforms, including non-Cys 34 modifications, exhibited lower FcRn binding affinity (33 μM K D ) than the high-affinity FcRn binding achieved with an HSA standard (20 μM K D ). Additionally, although Cys 34 oxidation (sulfinic acid) was detected in the low-affinity fraction, the predominant low-affinity fraction Cys 34 adduct was cysteinylation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, one of the major albumin modifications, glycosylation, leads to reduced affinity with FcRn. This, in turn, reduces transcytosis and increases intracellular catabolism, resulting in the excretion of albumin fragments and rapid vascular clearance [75,76]. It should be noted, among the investigated modifications (Lys525, Lys195, and Lys233), only Lys525, which alters the conformation changes in domain III, decreases HSA-FcRn binding.…”
Section: Binding Of Receptors To Albuminmentioning
confidence: 98%
“…Precisely, the loops I and II of DI and DIII nearby Lys466 are in proximity with the receptor. Therefore, the chemical or posttranslational modification in such sites and ligand binding possibly leads to conformation changes, lower FcRn binding, and better albumin degradation in lysosomes; for example, Cys34 (DI domain) oxidation, cysteinylation, or cysteinylglycinylation act negatively on HSA-FcRn interaction [75]. Moreover, one of the major albumin modifications, glycosylation, leads to reduced affinity with FcRn.…”
Section: Binding Of Receptors To Albuminmentioning
confidence: 99%
“…Glycation of serum albumin is a known modification that occurs in circulation, especially in disease states such as diabetes. Recent studies have shown that the interaction of glycated albumin, particularly at position K525, leads to a reduction in affinity for FcRn (Leblanc et al, 2019). Molecules involving albumin fusions may require a deeper characterization to understand the PK impact in certain clinical populations.…”
Section: Metabolismmentioning
confidence: 99%